Bioenergy and agriculture: Promises and challenges: Environmental effects of bioenergy - Kartha, Sivan (International Food Policy Research Institute, 2006)
As concerns about climate change and energy security rise, bioenergy is often proposed as a renewable energy source that can be cost-effectively scaled up to a level that would allow it to contribute significantly to meeting global energy demand. Given that bioenergy can be generated in myriad ways, however, using various feedstocks and various energy technologies, few universal conclusions can be drawn about its environmental effects. One can easily imagine biomass production systems that are ideally suited to their environment, and even contribute to improving the environment by revegetating barren land, protecting watersheds, providing habitat for local species, and sequestering carbon, all while contributing to livelihoods of rural communities. Yet one can just as easily imagine biomass production systems that are fossil fuel intensive, exhaust the soil of nutrients, exacerbate erosion, deplete or degrade water resources, reduce biodiversity by displacing habitat, increase greenhouse gas emissions, and threaten the livelihoods of local communities. As with agricultural pursuits generally, the net impact of a bioenergy critically depends on how it is generated.